2013
DOI: 10.1165/rcmb.2012-0397oc
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulation of Nonmuscle Myosin Light Chain Kinase Expression in Human Lung Endothelium

Abstract: Increased lung vascular permeability, the consequence of endothelial cell (EC) barrier dysfunction, is a cardinal feature of inflammatory conditions such as acute lung injury and sepsis and leads to lethal physiological dysfunction characterized by alveolar flooding, hypoxemia, and pulmonary edema. We previously demonstrated that the nonmuscle myosin light chain kinase isoform (nmMLCK) plays a key role in agonist-induced pulmonary EC barrier regulation. The present study evaluated posttranscriptional regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 57 publications
4
33
1
Order By: Relevance
“…Previously, we indicated that expression of the broadly conserved mature miR-374a (50) is significantly decreased by 18% CS, TNF-a, or LPS (37). We now demonstrate that miR-568 is expressed in ECs with significant down-regulation by 18% CS and LPS (Figure 2).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Previously, we indicated that expression of the broadly conserved mature miR-374a (50) is significantly decreased by 18% CS, TNF-a, or LPS (37). We now demonstrate that miR-568 is expressed in ECs with significant down-regulation by 18% CS and LPS (Figure 2).…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, we found that PBEF/NAMPT expression in ECs is markedly up-regulated at mRNA and protein levels in response to 18% CS and LPS (Figure 1). Our combined data (37,39,51) demonstrate the negative correlation between expression levels of putative miRNA and mRNA/protein and suggest that down-regulation of these miRNAs may contribute to augmented PBEF/NAMPT gene expression in ECs treated with these proinflammatory agonists. To further evaluate whether miR-374a and miR-568 specifically regulate PBEF/NAMPT expression in ECs, transfection with synthetic miRNA mimics and antagomirs was used.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Even if these data are referred to the mucosal level of the enzymes, we cannot exclude that a similar mechanism could be present in the muscle layer (which include several cell types) and account, together with protection of muscle cells from oxidative stress, for the prevention of contractility impairment of the entire muscle strips. The rapid increase in MLCK transcript is in agreement with previous reports, showing that LPS treatment leads to a quick induction of MLCK mRNA in lung endothelial cells [49]. …”
Section: Discussionsupporting
confidence: 93%
“…33 Loyer et al clearly demonstrated that in vivo inhibition of miR-92a in ldlr −/− mice restricted the development of AS. 33 Loyer et al clearly demonstrated that in vivo inhibition of miR-92a in ldlr −/− mice restricted the development of AS.…”
Section: Discussionmentioning
confidence: 99%